Effect of Intravaginal Clindamycin Cream on Pregnancy Outcome and on Abnormal Vaginal Microbial Flora of Pregnant Women - Isobel J. Rosenstein; D. John Morgan; Ronald F. Lamont; Marie Sheehan; Caroline J. Doré; Phillip E. Hay; David Taylor-Robinson (Hindawi Limited, 2000)
Objectives: To determine whether intravaginal clindamycin cream reduces the incidence of abnormal pregnancy outcome in women with abnormal vaginal microbial flora graded as intermediate or BV and to investigate the effect of the antibiotic on vaginal microbial flora.